Hubungan Aktivitas Fisik dengan Keluhan Dismenore Primer pada Mahasiswi Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warmadewa - Ni Made Ayu Pratiwi Wedantari; Komang Trisna Sumadewi; I Gusti Ngurah Suryantha (Aesculapius Medical Journal, 2023)
Dysmenorrhea is a gynecological health complaint. The incidence of dysmenorrhea was 1,769,425 people, 90% of women. The highest prevalence of dysmenorrhea was experienced by female students with a percentage of 34.2% including severe pain; 36.6% had moderate pain; and 29.2% had mild pain. In previous studies, the majority of medical students had lack of physical activity due to tight lecture schedules. Physical activity is known to have a role in producing endorphins which are the body's natural painkillers. This study aims to determine whether there is a relationship between physical activity and primary dysmenorrhea in female students of the Faculty of Medicine and Health Sciences, Warmadewa University. Sampling was carried out at the Faculty of Medicine and Health Sciences, Warmadewa University, Denpasar City, Bali Province. The time for the research is on October 2022. This research used analytic method with cross sectional design. The sampling technique for this study used simple random sampling amounted 100 respondents. Data collection used the International Physical Activity Questionnaire (IPAQ) and dysmenorrhea questionnaire. Data analysis used the Chi Square test. The results showed that the prevalence of low physical activity was 43% and primary dysmenorrhea was 75%. The results of the Chi Square test obtained p-value = 0.000 so that it can be concluded that there is a significant relationship between physical activity and complaints of primary dysmenorrhea in female students of the Faculty of Medicine and Health Sciences, Warmadewa University.